Exploiting the reciprocal channel for discrete jamming to secure wireless communications against multiple-antenna eavesdropper - Anjos, Gustavo (2020)
The purpose of this paper is to advance the current state of physical layer security through the design and analysis of a discrete jamming scheme that exploits the reciprocal characteristic of the wireless channel with the aim to create equivocation to a passive multiple-antenna eavesdropper. Closed form solutions of the secrecy capacity for different configurations of the jamming component were obtained and successfully compare with the simulation results. Furthermore, the secrecy level provided by the developed scheme is analyzed taking into account the number of bits extracted from the channel. The asymptotic study of the proposed secrecy technique allowed to conclude that in the high-power regime, full secrecy is obtained even considering that the eavesdropper is equipped with an unlimited number of antennas.